Scanned-wavelength intra-cavity QEPAS sensor with injection seeding technique for C2H2 detection. (December 2019) - Zhang, Qinduan; Chang, Jun; Cong, Zhenhua; Feng, Yiwen; Wang, Zongliang; Sun, Jiachen
Highlights: A scanned-wavelength intra-cavity QEPAS sensor with injection seeding technique and Q-switched technique was reported. The Q-switched fiber laser has a peak pulse power of 0.88 W. A minimum detection limit (MDL) of 507 ppbv was achieved. Abstract: A high sensitivity scanned-wavelength intra-cavity quartz enhanced photoacoustic spectroscopy (QEPAS) system, based on injection seeding technique and Q-switched technique, was proposed in this paper. In this system, the gas cell was placed in the acousto-optic Q-switched fiber laser cavity, and the high power Q-switched pulses were used to acoustic wave excitation. A distributed feedback (DFB) diode laser with a wavelength scanning range from 1532.63 nm to 1533.03 nm was used as the seed laser to select the laser wavelength. The laser power emitted by the seed laser operating at an injection current of 56 mA (the gas absorption peak) was 3 mW. A custom-made broadband fiber Bragg grating (FBG) with a bandwidth of 500 pm (picometer) was used to stabilize the cavity operation and suppress the amplified spontaneous emission (ASE) spectrum. With an intra-cavity peak pulse power of 0.88 W, the system achieved a minimum detection limit (MDL) of 507 ppbv at atmospheric pressure and room temperature, corresponding to a normalized noise-equivalent absorption (NNEA) of 1.616 × 10 −8 W cm −1 Hz −1/2 .